2018
DOI: 10.1136/annrheumdis-2017-212379
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation mapping identifies gene regulatory effects in patients with systemic lupus erythematosus

Abstract: ObjectivesSystemic lupus erythematosus (SLE) is a chronic autoimmune condition with heterogeneous presentation and complex aetiology where DNA methylation changes are emerging as a contributing factor. In order to discover novel epigenetic associations and investigate their relationship to genetic risk for SLE, we analysed DNA methylation profiles in a large collection of patients with SLE and healthy individuals.MethodsDNA extracted from blood from 548 patients with SLE and 587 healthy controls were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
115
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(129 citation statements)
references
References 43 publications
12
115
0
2
Order By: Relevance
“…While most epigenetic studies in lupus have been performed in T cells, there is evidence to suggest reduced DNA methylation levels in multiple cell types in this disease. For example, a robust demethylation signature in interferon-regulated genes in lupus is wide-spread and characteristic of the disease [4][5][6].…”
mentioning
confidence: 99%
“…While most epigenetic studies in lupus have been performed in T cells, there is evidence to suggest reduced DNA methylation levels in multiple cell types in this disease. For example, a robust demethylation signature in interferon-regulated genes in lupus is wide-spread and characteristic of the disease [4][5][6].…”
mentioning
confidence: 99%
“…However, elucidating the causal genes underlying GWAS hits remains challenging given the complexities of a typical genome-wide significant locus and the regulatory process. [25][26][27] Our study identified hundreds of DNA methylations that were associated with SLE. On the other hand, although traditional case-control studies have identified DNA methylations 25 and gene expressions [19][20][21][22] implicated in the pathogenesis of SLE, the power is very limited because of the small sample size.…”
Section: Discussionmentioning
confidence: 88%
“…Laboratory-based evaluation of all of the genes in the associated regions is costly and hard to achieve at this stage. 26 These methylations were supposed to affect UBE2L3 expression (needs to be proven). Moreover, traditional observational studies are subject to confounding and reverse causation and have not been able to disentangle which genetic, epigenetic and other factors directly influence SLE.…”
Section: Discussionmentioning
confidence: 99%
“…One of these cytokines is IFN‐α, a multipotent type of IFN, characterized by disrupting immune tolerance, activating autoreactive T and B cells and enhancing the autoimmune response . Human interferon regulatory factor (IRF)5 gene is mapped to the chromosome 7q32 . There are nine exons in the IRF5 gene.…”
Section: Introductionmentioning
confidence: 99%
“…3 Human interferon regulatory factor (IRF)5 gene is mapped to the chromosome 7q32. 4 There are nine exons in the IRF5 gene. It has a CpG island, encompassing exons 1A and 1B.…”
mentioning
confidence: 99%